Examining global phenomena of poverty and inequality through The Poverty Line project - Lin, Huiyi (Design/Arts/Culture, 2023)
The Poverty Line project started from a question: “What does it mean to be poor?” In 2010, we began creating art examining the global phenomena of poverty and inequality. From our observations, and our respective backgrounds of economics (Lin) and photography (Chow), we discussed the complexities of the issues in different places we lived in or visited. Our ideas were distilled into representing the daily food choices one would face living at the poverty line of a country. From 2010 to 2020, we traveled 200,000 kilometers to create case studies of 36 countries and territories spanning six continents. We used each country’s official poverty definition to derive a per-person, per-day rate. For middle- and high-income economies, the average low-income household food expenditure is taken into account, while for low-income economies, the entire daily income of a poor individual is used. According to the granted sum of money, food is bought in local marketplaces. Each product is photographed on a local newspaper from the day of the shoot. Through the research, creation and engagement, we expanded our understanding and questions. We realized and broke down assumptions about poverty and inequality, and gathered ideas about food systems and vulnerabilities.